2008
DOI: 10.1080/09585190802324304
|View full text |Cite
|
Sign up to set email alerts
|

The gap between research and practice: a replication study on the HR professionals' beliefs about effective human resource practices

Abstract: In 2002 Rynes, Colbert and Brown asked human resource (HR) professionals to what extent they agreed with various HR research findings. Responses from 959 American participants showed that there are large discrepancies between research findings and practitioners' beliefs about effective human resource practices. The current research is a replication of the Rynes et al. study among 626 Dutch HR professionals. The results show remarkable similarities with the American study: there are large discrepancies between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 13 publications
9
62
0
1
Order By: Relevance
“…Trainers also reported that they prefer to attend more academic programs and academic conferences and talk more with academics than they do now, and they prefer to attend fewer internal training programs than they do currently. This finding is consistent with Rynes et al (2002) and Sanders et al (2008), who reported that HR professionals would prefer to talk to academics about HR problems. As such, trainers' preferred learning methods revealed less desire to learn on the job (e.g., perhaps via trial-and-error learning), less desire to interact with internal trainers, less reliance on Web searches, and less use of the training literature.…”
Section: Learning Methodssupporting
confidence: 94%
See 1 more Smart Citation
“…Trainers also reported that they prefer to attend more academic programs and academic conferences and talk more with academics than they do now, and they prefer to attend fewer internal training programs than they do currently. This finding is consistent with Rynes et al (2002) and Sanders et al (2008), who reported that HR professionals would prefer to talk to academics about HR problems. As such, trainers' preferred learning methods revealed less desire to learn on the job (e.g., perhaps via trial-and-error learning), less desire to interact with internal trainers, less reliance on Web searches, and less use of the training literature.…”
Section: Learning Methodssupporting
confidence: 94%
“…Replications of the Rynes et al (2002) study uncovered similar results. For example, in a study of 626 Dutch HR practitioners (Sanders, van Riemsdijk, & Groen, 2008), professional HR (Dutch) journals were read more frequently than academic journals. Still, however, only three professional journals were read more than "sometimes."…”
Section: Literature Sources and Perceived Utilitymentioning
confidence: 98%
“…Similar patterns of disparities were found in other countries such as the Netherlands (Sanders, van Riemsdijk, & Groen, 2008) and the United Kingdom (Guest, 2007). Sanders, van Riemsdijk, and Groen (2008) replicated the study by with 626 Dutch HR professionals.…”
Section: Introductionsupporting
confidence: 74%
“…Sanders, van Riemsdijk, and Groen (2008) replicated the study by with 626 Dutch HR professionals. They found that many HR professionals in the study also had beliefs that were in contrast to research findings on effective HR practices.…”
Section: Introductionsupporting
confidence: 64%
“…The stimulation of theory and good practice and bridging the well-documented gap between research and HRM practice could contribute to the effectiveness of HRM, which, in turn, could add value to organisational performance and functioning (Sanders, Van Riemsdijk & Groen, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%